Autism, language delay and mental retardation in a patient with 7q11 duplication. Issue 7 (30th March 2007) - Depienne, C; Heron, D; Betancur, C; Benyahia, B; Trouillard, O; Bouteiller, D; Verloes, A; LeGuern, E; Leboyer, M; Brice, A
Abstract : Background: Chromosomal rearrangements, arising from unequal recombination between repeated sequences, are found in a subset of patients with autism. Duplications involving loci associated with behavioural disturbances constitute an especially good candidate mechanism. The Williams–Beuren critical region (WBCR), located at 7q11.23, is commonly deleted in Williams–Beuren microdeletion syndrome (WBS). However, only four patients with a duplication of the WBCR have been reported to date: one with severe language delay and the three others with variable developmental, psychomotor and language delay. Objective and Methods: In this study, we screened 206 patients with autism spectrum disorders for the WBCR duplication by quantitative microsatellite analysis and multiple ligation-dependent probe amplification. Results: We identified one male patient with a de novo interstitial duplication of the entire WBCR of paternal origin. The patient had autistic disorder, severe language delay and mental retardation, with very mild dysmorphic features. Conclusion: We report the first patient with autistic disorder and a WBCR duplication. This observation indicates that the 7q11.23 duplication could be involved in complex clinical phenotypes, ranging from developmental or language delay to mental retardation and autism, and extends the phenotype initially reported. These findings also support the existence of one or several genes in 7q11.23 sensitive to gene dosage and involved in the development of language and social interaction.